Diversity of Diptera species associated with pig carcasses in a Brazilian city exposed to high rates of homicide - Cruz, Tadeu Morais; Barbosa, Taciano Moura; Thyssen, Patrícia Jacqueline; Vasconcelos, Simão Dias (Papéis Avulsos de Zoologia, 2021)
Cities in northeastern Brazil experience extreme rates of unsolved homicides, a situation that stimulates innovative procedures in the police work, such as forensic entomology. We surveyed necrophagous insects associated with carrion in a city exposed to high rates of homicides in Northeastern Brazil. The experiments were carried out in a rainforest fragment located in Recife, State of Pernambuco. Two pig carcasses were used as models, one in the dry and the other in the rainy season. The collection of adults was performed daily until the complete skeletonization of the carcasses. At least 32 Diptera species from the families Calliphoridae, Muscidae, Sarcophagidae, Fanniidae, Phoridae, Anthomyiidae, Piophilidae, and Stratiomyidae were registered, some of which have been previously documented on cadavers. A high richness of Diptera species was registered in all stages of decomposition. A strong overlap in the occurrence of most species was observed, which invalidates a defined entomological succession on the carcasses. Two species stood out in terms of abundance: Ophyra chalcogaster (Muscidae) and Chrysomya albiceps (Calliphoridae). The ubiquity of Hemilucilia semidiaphana (Calliphoridae) seems to confirm its preference for forest fragments exposed to low anthropogenic action. Our data contribute to expand the knowledge on the geographical distribution of forensically relevant species in the region and confirm the rapid dissemination of invasive Chrysomya species in forested areas.